Kontruktivisme Sosial Dalam Pembelajaran Kolaboratif di Kalangan Mahasiswa - Erni Dina; Abdul Khobir; Laelik Nur Kholisoh; Abdy Cahya Subekti (Yayasan Al-Afif, 2025)
This research focuses on a deeper understanding of the concept of social constructivism and how this theory is applied in teaching methods. This study uses a conceptual approach by collecting various data from reliable secondary sources. The research findings indicate that social constructivism, developed by important figures such as Jerome Bruner and Lev Vygotsky, emphasizes that students' knowledge is formed through language, culture, and social interaction. This means that students learn not only from individual thinking but also from the process of interacting with others. In teaching practice, the principles of social constructivism are evident through activities such as class discussions, small group collaboration, and active student engagement during the learning process. When cognitive aspects (students' ways of thinking) are combined with social aspects, a more dynamic, collaborative, and inclusive learning environment is created. Overall, this theory views learning as a social activity, in which each student plays a key role in constructing their own understanding and knowledge.